The Jungle Book - Kipling, Rudyard (MDS Books/ MEDIASAT, 2003)
This is a classic collection of fables with animal characters used to teach moral lessons. Among the most famous are the stories of Mowgli, a 'man-cub' raised by wolves in the Indian jungle; that of Rikki-Tikki-Tavi, a heroic mongoose; and 'Toomai of the Elephants', the story of a young elephant-handler.
Keywords: Juvenile literature-Classics (Kipling)-India-Jungles-Animals -Mowgli (Fictitious character)